STUDENTS’ DROPOUT AT THE SECONDARY LEVEL OF EDUCATION IN BANGLADESH: A CASE STUDY OF NAWABGANJ GOVT. PILOT HIGH SCHOOL & COLLEGE AT KALAKOPA UNION OF NAWABGANJ UPAZILA - Hasan, Mohammad Mehedi; Surjamokhey, Sabina Yasmin (Bangladesh Journal of Multidisciplinary Scientific Research, 2022)
Education is a staircase that moves us from the darkness to light and leads us to a new height. Education removes our inner ignorance and broadens our minds and outlook. Bangladesh has made outstanding progress in the education sector. The Government of Bangladesh has been able to restrain the dropout rate at the primary level of education but needs to check the dropout rate at the secondary level. It is still alarming. So, it is necessary to study the issue to know the real picture of the students’ dropouts. The study examines the causes behind students’ dropout and to understand the current status of students’ dropout at Nawabganj Govt. Pilot High School & College. The study employs a simple random sampling process through interviews to collect the primary data based on qualitative research. The result of the study reveals mainly the ignorance of parents, parents’ unconsciousness, poverty, child labor, migration, lack of adequate facilities, lack of quality education, early marriage, eve-teasing, disobedience to parents, addiction to mobile phone and internet as well as addiction to drugs are the leading causes of students’ dropout. The study’s finding suggests that to mitigate or eradicate the dropout of students, there should be some necessary steps like- increasing parental awareness and activity, confirming adequate sports arrangements at the school, ensuring a beautiful environment for education, and enhancing stipends facilities for the poor and meritorious students. JEL Classification Codes: G32, F65, L66, L25, M41.